Drug delivery strategies to improve the treatment of corneal disorders - Mahsa Fallah Tafti; Zeinab Fayyaz; Hossein Aghamollaei; Khosrow Jadidi; Shahab Faghihi (Heliyon)
Anterior eye disorders including dry eye syndrome, keratitis, chemical burns, and trauma have varying prevalence rates in the world. Classical dosage forms based-topical ophthalmic drugs are popular treatments for managing corneal diseases. However, current dosage forms of ocular drugs can be associated with major challenges such as the short retention time in the presence of ocular barriers. Developing alternative therapeutic methods is required to overcome drug bioavailability from ocular barriers. Nanocarriers are major platforms and promising candidates for the administration of ophthalmic drugs in an adjustable manner. This paper briefly introduces the advantages, disadvantages, and characteristics of delivery systems for the treatment of corneal diseases. Additionally, advanced technologies such as 3D printing are being considered to fabricate ocular drug carriers and determine drug dosages for personalized treatment. This comprehensive review is gathered through multiple databases such as Google Scholar, PubMed, and Web of Science. It explores information around ''ocular drug delivery systems'', ''nano-based drug delivery systems'', ''engineered nanocarriers'', and ''advanced technologies to fabricate personalized drug delivery systems''.